Determinants of Overweight Among Primary School Children in Arba Minch Town, Southern Ethiopia, 2021 - Ezo E; Gashawbeza B (Dove Medical Press, 2021)
Elias Ezo,1 Biruk Gashawbeza1,2 1Department of Comprehensive Nursing, College of Medicine and Health Sciences, Wachemo University, Hosanna, Ethiopia; 2Department of Public Health, Paramed College, Arba Minch, EthiopiaCorrespondence: Elias Ezo Email eliasezo805@gmail.comBackground: The condition of being overweight is the abnormal excessive accumulation of fat in the body. Globally, it is a serious public health issue in both developing and developed countries.Objective: This study aims to identify determinants of overweight among primary school children in Arba Minch town, Southern Ethiopia, 2021.Methods: A school-based unmatched case control study was conducted from June 20 to 30, 2021. The total sample size was 285 (95 cases and 190 controls). Multistage sampling technique was used. Data were entered using Epi data 3.1 version and analyzed using SPSS version 24 software. Frequency, tables and figures were used. Bivariable analysis was done and variables with p < 0.025 were entered to multivariable logistic regression analysis. Statistical significance was declared at p < 0.05 with 95% confidence interval (CI).Results: The odds of overweight increased 19.8 times more in children whose fathers work in private business [AOR: 19.82, 95% CI: 6.21, 63.25], increased 4.8 times more in children who consume meat on more than 2 days per week [AOR: 4.75, 95% CI: 1.61, 14.03], increased 5 times more in children who consume milk on more than 2 days per week [AOR: 5.02, 95% CI: 1.80, 13.98], increased 11.9 times more in children who spend more than 6 hours sitting per day [AOR: 11.89, 95% CI: 4.13, 34.28]. And also, odds decreased by 84% in children who consume fruit on more than 2 days per week [AOR: 0.07, 95% CI: 0.03, 0.19], decreased 93% in children who consume vegetables on more than 2 days per week [AOR: 0.16, 95% CI: 0.06, 0.42], decreased 67% in children who consume cereals on more than 2 days per week [AOR: 0.33, 95% CI: 0.13, 0.84].Conclusion: Fathers working in private business, consuming fruit, vegetables, cereals, meat and milk on more than 2 days per week and sitting for more than 6 hours per day were determinants for overweight in this study. Therefore, it is better to include fruit, vegetables and cereals in dietary habits, decrease consumption of meat and milk and minimize sitting to less than 6 hours per day including school learning time.Keywords: overweight, children, elementary school